Women’s Image as Presented in Vitamin Drink’s Commercials: Semiotics Analysis on YOU C-1000 and Hemaviton C1000 - Amanah Risaningtyas; Wahyu Kartika Wienanda (JLA (Jurnal Lingua Applicata), 2021)
Several studies have identified women's image in beverage advertisements, but there has been not much research into the women’s image presented in vitamin drink commercials along with their slogans. This study focuses on an analysis of verbal and non-verbal signs of 2 vitamin drink commercials, namely YOU C1000 and Hemaviton C1000, from YouTube. Qualitative content analysis based on Peirce’s (1940) semiotics theory was used to analyse the verbal and non-verbal signs presented in the commercials, while the image of women proposed by Hung & Li (2006) was used to identify women’s image in the commercials. The findings suggest that in general, the commercials have tried to break the common traditional stereotypes of women’s image, even though some parts were still a bit stereotypical. The most common women’s image shown in the video is ‘a strong woman’. Moreover, the slogans of YOU C1000 and Hemaviton C1000 are trying to show that women can also do outdoor activities. The finding indicates that there is an attempt to change the way of presenting women in today’s advertisements.